CLINICAL PROFILE AND OUTCOME OF CHILDREN WITH SEVERE ACUTE MALNUTRITION ADMITTED AT NUTRITIONAL REHABILITATION CENTER OF MCCH-ASSOCIATED HOSPITAL OF GMC-ANANTNAG - MAJID, ANDLEEB; HUSSAIN, MALIK SHAKIR; NAJAR, BILAL AHMAD; TALI, SHOWKAT HUSSAIN; GULZAR, SUMAIRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were to study the clinical profile and outcome of children Admitted in NRC of MCCH-associated hospital of GMC-Anantnag. Methods: Children in the age group of 1 month-5 years, admitted to NRC of our hospital between April 2019 and May 2022 with severe acute malnutrition (SAM) were enrolled for the study. As per a predesigned pro forma, a detailed history was taken from mothers or caregivers and nutritional status assessment using standard anthropometric methods was performed. Classification of malnutrition was made according to the WHO guidelines. Anthropometric measurements including weight in kg and length/height in cm, weight for height, Z score, mid-upper arm circumference, and presence of edema were used to classify the grades of malnutrition. After basic workup and starting nutrition rehabilitation, serial weight gain was recorded. Outcome of patients (home discharge, referral to higher center, and death) was recorded and analyzed. Results: A total of 306 children with SAM admitted to NRC of our hospital were enrolled for the study. Majority were of 7–12 months of age (n=93; 30.4%), of female gender (n=178; 58.2%), were from nuclear families and from families with spacing between two children <2 years. SAM was more among children of illiterate and unskilled parents and of parents in the lower and upper lower socioeconomic status (288, 94%). Acute gastroenteritis (n=206; 67.32%) and acute respiratory tract infection (n=158; 51.6%) were most predominant comorbidities seen among hospitalized children. Hypoglycemia (n=183; 59.80%) and hypokalemia (n=56; 18.30%) were most common metabolic derangements. Among the admitted children 119 (38.88%) had good weight gain (10 mg/kg/day), 136 (44.44%) had moderate weight gain (5-10gm/kg/day) and 51 (16.66%) had poor weight gain (<5 g/kg/day). Out of 306 children admitted, 276 (91%) children were discharged after successful rehabilitation and 27 (9%) were transferred to higher center. No death was documented among SAM children during the study period. Conclusion: Malnutrition in under five children is high and multi-factorial. Hospital-based management of SAM is an important step in reducing the morbidity and mortality among such children.